1984
DOI: 10.1016/s0140-6736(84)91876-2
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Liver Transplantation in a Patient With Familial Hypercholesterolaemia

Abstract: A girl aged 6 years 9 months with severe heart disease secondary to homozygous familial hypercholesterolaemia underwent orthotopic cardiac transplantation and her liver was replaced with the liver of the same donor. In the first 10 weeks after transplantation serum cholesterol fell to 270 mg/dl from preoperative concentrations of more than 1000 mg/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
138
0
7

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(147 citation statements)
references
References 8 publications
(8 reference statements)
0
138
0
7
Order By: Relevance
“…The first use of liver transplantation to treat FH was with combined heart-liver transplantation, and as predicted, the plasma LDL cholesterol concentrations fell. 6 The present case is the second liver transplantation in FH to be reported.At age 18 months a yellowish xanthoma was first detected on the left ankle of patient V.P. Subsequent evaluation of blood cholesterol levels of the entire family was consistent with diagnosis of homozygous FH.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The first use of liver transplantation to treat FH was with combined heart-liver transplantation, and as predicted, the plasma LDL cholesterol concentrations fell. 6 The present case is the second liver transplantation in FH to be reported.At age 18 months a yellowish xanthoma was first detected on the left ankle of patient V.P. Subsequent evaluation of blood cholesterol levels of the entire family was consistent with diagnosis of homozygous FH.…”
mentioning
confidence: 73%
“…The first use of liver transplantation to treat FH was with combined heart-liver transplantation, and as predicted, the plasma LDL cholesterol concentrations fell. 6 The present case is the second liver transplantation in FH to be reported.…”
mentioning
confidence: 73%
“…Liver transplantation, as a curative treatment of homozygous for FH, was introduced in 1984 9) because approximately 70% of LDL receptors are located in the liver. Deceased donor graft can provide the effective therapy for the recipient.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 The liver transplant was performed to correct the genetic defect in hepatic metabolism responsible for her heart disease. Follow-up studies have demonstrated successful correction of the metabolic defect.…”
Section: Multiple Organ Transplantsmentioning
confidence: 99%